Tailoring polypyrrole supercapacitive properties by intercalation of graphene oxide within the layer. (1st March 2016) - SaĿer, D.; Ŀapeta, D.; Šrut RakiĿ, I.; Peter, R.; PetraviĿ, M.; KraljiĿ RokoviĿ, M.
Abstract: In this work polypyrrole was prepared using different solutions of graphene oxide as the supporting electrolyte. Two different samples of graphene oxide (GO1 and GO2) were prepared from different graphite precursors. The obtained samples were characterised by means of scanning electron microscope (SEM), atomic force microscope (AFM) and X-ray photoemission spectroscopy (XPS), which showed a significant difference between the two structures considering their morphology characteristics, sheet size and type of oxygen functionalities. However, all the graphene oxide samples used in this work contain appropriate amounts of COO ⿿ groups essential for compensation of positive charge generated at the polymer backbone. The polymer layers were prepared by cyclic voltammetry and chronoamperometry methods from GO1 (PPy/GO1), GO2 (PPy/GO2) and dialysed GO2 (PPy/D-GO2) supporting electrolyte solutions. The examinations were carried out in appropriate graphene oxide or Na2 SO4 solutions. The results obtained reveal that the layers are electrochemically active in graphene oxide solution. However, the polymer response is significantly improved in Na2 SO4 solution. Electrochemical quartz crystal nanobalance (EQCN) measurements suggest that graphene oxide is involved in the polypyrrole redox reaction while the morphology characteristics suggest that graphene oxide is incorporated within the polymer layer. The properties of the layer depend on the type of graphene oxide solution used during the synthesis. The specific capacitance value of the PPy/D-GO2 layer prepared by the chronoamperometry method was found to be dependent on the deposited material mass and for 1.20 to 0.38 μg of polypyrrole it ranged between 149.51 and 221.76 F g ⿿1, respectively.